The drivers of firm longevity: Age, size, profitability and survivorship of Australian corporations, 1901–1930. Issue 2 (17th February 2018) - Panza, Laura; Ville, Simon; Merrett, David
Abstract: Why do some firms last longer than others? This question has attracted considerable interest among scholars from business history, management and economics. Our article combines the business historian's macro view of the relationship between size, longevity, and economic development with quantitative modelling. We apply survival analysis to data relating to size, age and profitability, three first-order explanations of longevity, for Australian stock exchange (ASX) listed corporations from 1901 to 1930. The novelty of the article is twofold: we find that firm size is a poor predictor of longevity for the full sample but its age and profitability are highly significant; our data covers a longer time frame and relates to a rich mid-sized and non-industrialised country.